2002
DOI: 10.1007/s00259-002-0950-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging cAMP-specific phosphodiesterase-4 in human brain with R -[ 11 C]rolipram and positron emission tomography

Abstract: Evidence of disruptions in cAMP-mediated signaling in several neuropsychiatric disorders has led to the development of R-[(11)C]rolipram for imaging phosphodiesterase-4 (PDE4) enzymes with positron emission tomography (PET). The high-affinity PDE4 inhibitor rolipram was previously reported to have an antidepressant effect in humans. PDE4 is abundant in the brain, and it hydrolyzes cAMP produced following stimulation of various neurotransmitter systems. PDE4 is regulated by intracellular cAMP levels. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…Among the cAMP-specific phosphodiesterases, PDE4 was found to be the predominant isoform in approximately two thirds of 60 human tumor cell lines (24). PDE4 is highly expressed in the brain (25) and can be specifically inhibited by rolipram. Rolipram is a particularly attractive agent for our purposes as it has been extensively evaluated in human clinical trials as an antidepressant and as an anti-inflammatory agent, including for inflammatory states of the central nervous system, such as multiple sclerosis (26,27).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Among the cAMP-specific phosphodiesterases, PDE4 was found to be the predominant isoform in approximately two thirds of 60 human tumor cell lines (24). PDE4 is highly expressed in the brain (25) and can be specifically inhibited by rolipram. Rolipram is a particularly attractive agent for our purposes as it has been extensively evaluated in human clinical trials as an antidepressant and as an anti-inflammatory agent, including for inflammatory states of the central nervous system, such as multiple sclerosis (26,27).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Recently, we have demonstrated that (R)-rolipram labeled with carbon-11 binds selectively in vivo in rat brain, heart and lung, and that this binding can be significantly reduced by PDE4 inhibitors, indicating presence of specific binding in these organs Lourenco et al, 2001). This tracer displayed potential for imaging the human brain with positron emission tomography (PET) (DaSilva et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The levels of cAMP and PDE4 are prone to vary with FMRP across the brain because the level by which FMRP expression is reduced can vary among FX brain regions (Taylor, Tassone et al 1999) and there is a direct correlation between levels of cAMP and FMRP (Berry-Kravis and Ciurlionis 1998). The extent to which cAMP and PDE4 levels vary with FMRP levels across brain regions could be studied with C 11 -rolipram using PET (DaSilva, Lourenco et al 2002). The cAMP defect would be expected to occur more in the cortex compared to other brain regions based on data from the Allen Brain Atlas (Lein, Hawrylycz et al 2007) which shows that FMR1 is primarily colocalized with AC type 5 in cortex (Figure 1).…”
Section: Cyclic Amp Theory Of Fragile Xmentioning
confidence: 99%